Spiritual Distress among Patients with Acute Coronary Syndrome in Cardiac Intensive Care Unit - Helda Fitria Wahyuni; Aan Nur'aeni; Afif Amir Amirullah (Universitas Padjadjaran, 2020)
Background. Engaging patients' spiritual needs with Acute Coronary Syndrome (ACS) is still primarily ignored compared to their physical needs. One thing that has been forgotten is spiritual distress assessment, even though the stress experienced can aggravate ACS conditions, especially in acute situations. This study aimed to identify spiritual distress among ACS patients in the Cardiac Intensive Care Unit (CICU). Methods. This study was a quantitative research with a population of ACS patients treated in CICU at one of the hospitals in West Java. The sampling technique used was consecutive sampling and obtained 34 respondents during one month. Collecting data using a modified instrument from the Spiritual Distress Assessment Tool (SDAT) and obtained a validity range of 0.33 - 0.45 and a reliability of 0.80. Data analysis using mean and frequency distribution. Results. 82.35% of respondents had mild spiritual distress, and 17.65% of respondents had moderate spiritual distress. The most disturbing spiritual distress was in the